FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA - Rofiqoh, Rofiqoh; Novika, Revi Gama Hatta; Sari, Andi Nur Indah; Idris, Idris (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Based on the 2022 Indonesian Nutrition Status Study Survey (SSGI), the prevalence of malnutrition in Indonesia is 7.7%. This figure has increased from 2021 which amounted to 7.1%. Meanwhile, in 2023 the prevalence of stunting reached 21.5%, wasting 8.5% and obesity reached 4.2%. According to data recorded in the Indonesian Health Survey report, the prevalence of children aged 0 to 23 months who are underweight in South Sulawesi Province shows a higher rate when compared to the national average of 12.6%. The purpose of the study was to determine the factors associated with the nutritional status of toddlers. The research design used in this study was Cross Sectional. The research was conducted in Untia Village, Biringkanaya Subdistrict, Sallodong Street, Makassar. The research was conducted in February 2024. The study population was all toddlers in Untia Village, Biringkanaya Subdistrict, Sallodong Street, Makassar City, totaling 257 toddlers. The sample amounted to 100 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between work (p value: 0.040) and income (p value: 0.000). It is recommended that the Puskesmas improve routine monitoring activities and periodic nutritional status assessments carried out in the Nutrition Post and Nutrition Clinic, and provide nutritional consultation guidance to mothers of children under five.Keywords: Toddler, Occupation, Income.